Rapid access to 7-substituted cycloalkylamino and alkylamino analogues of 4-methylcoumarin reveals surprising emitters - Das S.; Goswami P.; Verma V.K.; Indurthi H.K.; Kumar M.; Koch B.; Sharma D.K. (My University, 2025)
Replacement of electron-donatingN,N-dialkyl groups with four-membered azetidine has recently been used as a promising approach to improve low fluorescent quantum yields of coumarin. Herein, we report the synthesis of 7-cycloalkylamino/alkyl amino analogues (6–19) from 4-methyl umbelliferone-derived nonaflate (1a’) using Buchwald-Hartwig amination and comparison of their fluorescence activity with 7-azetidinyl-4-methylcoumarin (4). The absolute quantum yields of cyclobutylamine (7), cyclopentylamine (8), propylamine (10), butylamine (11), isopropylamine (16), and isobutylamine (17) were found to be comparable to that of the azetidine (4) coumarin. Further, the dyes were found to be biocompatible in cell lines. Also, the successful application of these new dyes in biological imaging for living cells has been demonstrated. © 2023 Elsevier Ltd